2021
DOI: 10.3390/jof7090737
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Keto-Acid Reductoisomerase ILVC in the Entomopathogenic Fungus Metarhizium robertsii

Abstract: Ketol-acid reductoisomerase (ILVC) is the second enzyme in the branched-chain amino acid (BCAA) biosynthesis, which regulates many physiological activities in a variety of organisms from bacteria to fungi and plants. In this work, function mechanisms of ILVC in Metarhizium robertsii Metchnikoff (Hypocreales: Clavicipitaceae) were explored with site-directed mutagenesis, reductase activity assays and transcriptomics analysis. The reductase activity assays showed that ILVC from phytopathogenic fungi exhibited si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…An inter-kingdom phylogenetic analysis revealed that BatA is part of a cluster among other fungal BATs (Figure S1, Table S8). In contrast, BatC grouped together with plant counterparts, and its gene is most likely plant-derived by HGT, as suggested for the other fungal leucine biosynthetic genes [4,31].…”
Section: Biochemical Characterization Of Batamentioning
confidence: 89%
“…An inter-kingdom phylogenetic analysis revealed that BatA is part of a cluster among other fungal BATs (Figure S1, Table S8). In contrast, BatC grouped together with plant counterparts, and its gene is most likely plant-derived by HGT, as suggested for the other fungal leucine biosynthetic genes [4,31].…”
Section: Biochemical Characterization Of Batamentioning
confidence: 89%
“…Upon the binding of cofactors, NADP(H) and Mg 2+ , the N-terminal domain of KARI undergoes large local conformational changes, only in the NADP(H) binding site. Four Mg 2+ -binding residues are also identified (D190, E194, E226, and E230) [19]. The side chains of these residues rotate upon metal ion binding.…”
Section: Phylogenetic Tree Based On Kari Sequence Between N Gonorrhoe...mentioning
confidence: 98%
“…Ketol-acid reductor-isomerase (KARI) is the second enzyme in the branched-chain amino acid (BCAA) biosynthesis, which regulates many physiological activities in a variety of organisms from bacteria to fungi and plants. The conservation in fungi but absence in mammals of the BCAA biosynthetic pathway makes it the target for herbicides, fungicides, and antimicrobial compounds [19]. KARI catalyzes the conversion of 2-acetolactate and 2-aceto-2-hydroxybutyrate to 2,3-dihydroxyisoverate and 2,3-dihydroxy-3-methyl valerate, respectively.…”
Section: Antimicrobial Resistance Mechanisms In N Gonorrhoeaementioning
confidence: 99%
See 1 more Smart Citation